STRATEGI BAURAN PEMASARAN ( MARKETING MIX ) DALAM PERSPEKTIF SYARIAH - Rahim, Endang; Mohamad, Roni (MUTAWAZIN (Jurnal Ekonomi Syariah), 2021)
Business activities are activities that require serious understanding, starting from planning what will be done, the implementation stage and the stage of monitoring a business being run. In running a business, the important task of marketers is to be able to provide what is needed by the community, both consumers and customers. In order for a business or business that is run to be successful, it would be nice to have an appropriate competitive strategy. This study aims to provide a study and analysis of the marketing mix strategy (Marketing Mix) in the sharia perspective. This type of research is a literature study, data is collected by conducting a review study of previous research journals that are relevant to this research.